If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13y = 4(3y + -7) Reorder the terms: 13y = 4(-7 + 3y) 13y = (-7 * 4 + 3y * 4) 13y = (-28 + 12y) Solving 13y = -28 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. 13y + -12y = -28 + 12y + -12y Combine like terms: 13y + -12y = 1y 1y = -28 + 12y + -12y Combine like terms: 12y + -12y = 0 1y = -28 + 0 1y = -28 Divide each side by '1'. y = -28 Simplifying y = -28
| 5m(2p-4q)= | | 5x+13=-15-9x | | 4x(y-2z)= | | x(9x+2)=7 | | 5m^2+14m-3=0 | | 20x^2-16x=48 | | 10-3x-4x+2x-12= | | 20x^2-16=48 | | p(4q+2r)= | | 4(x+2)=32 | | z+8=3z | | (x+5)(x+2)= | | 2x+9=x+73 | | -(7y+2)-(-6y-4)=1 | | 2a(3b+2c)= | | 5x-x-2x+8-3x=0 | | 0.30(12)+0.05x=0.15(12+x) | | 5x-x-2x+8-3d=0 | | 3x(4y+2z)= | | 6(3x-1)-18x= | | 6(x-4)=8(x-2) | | 4(y+2)=33 | | 2=6x-8-5x | | -3y+3=4y+8 | | 2+3=12.00+16.95 | | -5(2p+4)-19=3(3p+6) | | 3+6x=13+6x | | -81+18y+5=6(4y-3)-4 | | 7x-10=59 | | (7*x)-10=59 | | 5(c-3)=6(c-7) | | 6*7x-8=7 |